Development of Organizational Psychology Module for Teachers at MTs Persis Lempong Garut - Ramadhan, Fahri Sahrul; Nugraha, Mulyawan Safwandy (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2024)
The purpose of this study is to develop an organizational psychology module that is specifically designed to meet the needs of teachers in improving collaboration and communication competencies at MTs Persis Lempong Garut. The method in writing this journal uses a qualitative method with a field research approach. This type of research is development research to produce products (modules). The researcher develops the module through the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. The data collection includes questionnaires, interviews, observations, and document studies. Furthermore, the results of the research findings are divided into several important points, including; a) Research results that include the development of organizational psychology modules, results and analysis (both qualitative and quantitative), b) Research discussion that includes module trials, results analysis, implications of findings, and contribution to results. So it can be concluded that the research on the development of the organizational psychology module at MTs Persis Lempong Garut has succeeded in fulfilling its goal of improving the understanding and management of organizational psychology in the context of education.